Releasing Emotions Through Art: Eggshell Art Therapy for Special Needs Students - Risnah Risnah; Nurfadilah Azmi; Alivia Nur Hidayah; Nur Salsabila (Direktorat Pengabdian kepada Masyarakat, 2026)
Art therapy is a nonverbal approach that utilizes creative processes to support emotional expression, attention regulation, and fine motor development among students with special needs. Senior high school students with intellectual disability and autism often experience difficulties in verbal communication, emotional regulation, sustained attention, and fine motor coordination, which may affect their learning engagement and daily functioning. This paper aims to describe the implementation of an art therapy program using three-dimensional whole eggshell decoration as a medium for nonverbal emotional expression while simultaneously stimulating focus and fine motor skills. The program was implemented as an art-based occupational therapy activity at a public special education school involving students aged 18–20 years. The activity design consisted of several stages, including preparation, decorating whole eggshells using paint, drawing facial expressions to represent daily emotional states, and simple reflection. Observations were conducted throughout the sessions to examine student participation, concentration, and motor control during the activity. The results indicate that students were able to actively engage in the sessions, maintain improved focus, and demonstrate better fine motor coordination while handling brushes and interacting with three-dimensional media. The facial expression drawings further reveal that the activity functioned as an effective medium for nonverbal emotional expression. In conclusion, the art therapy program using whole eggshell decoration offers a practical, low-cost, and innovative alternative for occupational therapy activities in special education settings, particularly in supporting emotional expression, focus, and fine motor stimulation among students with intellectual disability and autism.